Mapping of antigenic domains of Sendai virus nucleocapsid protein expressed in Escherichia coli. - Gill, D S (1988)
Several nonoverlapping epitopes were mapped on the primary sequence of the Sendai virus NP protein. After a complete cDNA clone of the Sendai virus NP gene was expressed in Escherichia coli, deletion constructs were used to generate a series of overlapping NP fragments deleted at their C termini. Immunoblot analyses with 11 monoclonal antibodies identified four antigenic sites. All of these sites resided in the C-terminal half of NP and were also the only sites detected with a polyclonal serum. These findings confirm and extend the evidence that the C terminus of the NP protein represents the domain exposed on the surface of the nucleocapsid. One of the monoclonal antibodies reacted with a site, comprising only 6 amino acids, lying with a hinge between an alpha-helix and a beta-strand in the predicted secondary structure of NP. Since this antibody is a potent inhibitor of in vitro viral RNA synthesis (K. L. Deshpande and A. Portner, Virology 139:32-42, 1984), the epitope may be critical to the flexibility of the NP molecule that makes the RNA template accessible during RNA synthesis.